The Emergence of Local Coffee Brands: A Paradigm Shift in Jakarta Coffee Culture - Kurniawan Arif Maspul (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2023)
This article delves into the burgeoning coffee market in Jakarta, Indonesia, to explore the factors that have propelled local coffee brands to success. It examines the cultural significance of coffee in Indonesian society, the increasing demand for specialty coffee, and the strategies employed by local brands to gain a competitive edge. Coffee has evolved beyond a mere beverage in Jakarta, becoming a symbol of cultural importance and a cherished tradition that unites people from diverse backgrounds. The article highlights the vibrant coffee culture in Jakarta, where coffee shops serve as social hubs, fostering connections and providing spaces for relaxation, intellectual discussions, and community engagement. It explores the coexistence of commercial and specialty coffee, with local brands catering to the diverse preferences of consumers. The article also delves into the strategies employed by local brands to cater to the demand for specialty coffee, including affordability, quality sourcing, and customization options. By understanding and adapting to the unique preferences of Jakarta's coffee culture, local coffee brands have emerged as significant players, shaping the future of the city's coffee industry. The research methodology involves interviews with industry professionals and the author's observations as a coffee professional and SCA trainer, providing valuable insights into Jakarta's specialty and commercial coffee landscape.